The Use of Testicular Sperm for Intracytoplasmic Sperm Injection in Patients with High Sperm DNA Damage: A Systematic Review - Rafael F. Ambar; Ashok Agarwal; Ahmad Majzoub; Sarah Vij; Nicholas N. Tadros; Chak-Lam Cho; Neel Parekh; Edson Borges Jr.; Sidney Glina (The World Journal of Men's Health, 2021)
The advent of intracytoplasmic sperm injection (ICSI) has changed the human reproduction landscape by overcoming several limitations related to both male and female infertility factors. However, despite the development of new technologies, the live-birth rate with ICSI has not exceeded 30%. In order to improve assisted reproductive technology outcomes, advanced sperm function analysis have gained increased attention and the effects of sperm DNA fragmentation (SDF) on assisted repro-duction success are being extensively studied. Utilizing ejaculated sperm with an elevated SDF has been found to result in poor ICSI outcomes. Furthermore, studies have reported that testicular sperm has lower SDF level, when compared to ejacu-lated sperm. This has led a number of clinicians world-wide to offer testicular sperm retrieval for ICSI in non-azoospermic males with high SDF. This practice has remained controversial due to lack of high quality evidence.